2020
DOI: 10.1007/s11892-020-01348-2
|View full text |Cite
|
Sign up to set email alerts
|

Do Women with Diabetes Need More Intensive Action for Cardiovascular Reduction than Men with Diabetes?

Abstract: Purpose of Review This narrative review makes the case for greater efforts to reduce cardiovascular disease (CVD) risk in women with diabetes. Recent Findings In a recent meta-analysis including five CVOTs of diabetes medications with 46,606 subjects, women (vs men) with type 2 diabetes had a higher relative risk for stroke (RR 1.28; 95% CI 1.09, 1.50) and heart failure (1.30; 1.21, 1.40). Prior studies found higher “within-gender” R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 69 publications
1
19
0
4
Order By: Relevance
“…In addition, some sex-specific studies found that certain risk factors and comorbidities were more potent in women 28. Diabetes mellitus, hypertension and smoking status are more strongly associated with increased risk of cardiac events in women compared with men 27 29…”
Section: Discussionmentioning
confidence: 99%
“…In addition, some sex-specific studies found that certain risk factors and comorbidities were more potent in women 28. Diabetes mellitus, hypertension and smoking status are more strongly associated with increased risk of cardiac events in women compared with men 27 29…”
Section: Discussionmentioning
confidence: 99%
“…This warrants a better understanding and identification of possible factors of influence in the young diabetes population. Among adults with diabetes, sex is recognised as a potent factor of influence, leading to increased attention for a tailored approach in men and women [6][7][8]. The importance of this approach is highlighted by the fact that female individuals with type 1 diabetes have an increased risk of all-cause mortality compared with male individuals, with vascular mortality being an important contributing force [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Caregiving responsibilities may partially explain sex and gender differences observed in adherence and responses to adherence interventions 22,23 . For example, compared to men with diabetes, women with diabetes have higher relative cardiovascular disease mortality risk which has been linked to lower rates of medication adherence and self‐management 22 .…”
Section: Discussionmentioning
confidence: 99%